Implementation of Law Number 33 Of 2014 in Halal Certification as Legal Protection for Muslim Consumers Maqashid Syariah Perspective: Implementation of Law Number 33 Of 2014 in Halal Certification as Legal Protection for Muslim Consumers Maqashid Syariah Perspective - Fansuri, Hamzah; Setyawan, Edy; Muamar, Afif; Bahomaid, Saleh Abdoalgaader Ali (Hikmatuna : Journal for Integrative Islamic Studies, 2025)
This research is motivated by the urgency of legal protection for Muslim consumers in Indonesia through halal certification, in line with the enactment of Law Number 33 of 2014 on Halal Product Assurance (UU JPH). The main objective of this study is to analyze the implementation of the UU JPH in halal certification practices and evaluate its effectiveness from the perspective of maqashid syariah. This research employs a normative juridical method using statute, conceptual, and maqashid-based approaches, and utilizes primary, secondary, and tertiary legal data, analyzed descriptively and analytically using content analysis techniques. The findings show that the implementation of the UU JPH is a strategic step in providing legal certainty regarding the halal status of products circulating in Indonesia. However, its execution still faces challenges, such as the low preparedness of small business actors and the limited number of halal auditors. Institutional strengthening and public education are needed to ensure more effective and equitable halal certification. Furthermore, this study affirms that the obligation of halal certification serves as a form of protection for the constitutional rights of Muslim consumers, guaranteed by national law and reinforced by administrative and criminal sanctions for violators. From the perspective of maqashid syariah, halal certification not only functions as a formal legal mechanism but also serves as an instrument to safeguard the fundamental values of human life. It ensures product compliance with sharia principles, preserves faith, health, and community welfare, and prevents moral and economic harm.